European inventory on validation of non-formal and informal learning 2010 : country report: Germany - Annen, Silvia [Verfasser]; Bretschneider, Markus [Verfasser] (My University, 2011)
Learning taking place outside the formal education and training system is crucially important for individuals, companies and society at large. Existing information about validation of non-formal and informal learning is, however, in most countries, scattered and not easily accessible. The European inventory aims to address this weakness by presenting regularly updated information on current practices in all countries taking part in the EU2020 cooperation process . The Inventory has been taken forward in a cooperation between the European Commission (DG EAC) and Cedefop. The 2010 version of the Inventory has been structured in such a way that it reflects and illustrates the European Guidelines on validation of non-formal and informal learning published. This country report provides an ovierview of the current situation as regards validation of non-formal and informal learning in Germany. (BIBB-Doku)
Keywords: L 2.1.1 Informelles Lernen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; Informelles Lernen; Anerkennung